Mechanistic insights into gut microbe derived siderophores and PHD2 interactions with implications for HIF-1α stabilization - Jainabbi Irshad Ahmed Patel; Jagadeesha Poyya; Apeksha Padakannaya; Namrata Manjunath Kurdekar; Ajay Sathayanarayan Khandagale; Chandrashekhar Gajanan Joshi; Santosh R. Kanade; Kapaettu Satyamoorthy (Scientific Reports)
Abstract In oxygen-deprived conditions, cells respond by activating adaptive mechanisms to bolster their survival and protect tissue integrity. A key player in this process is the HIF-1α signaling cascade, meticulously regulated by Prolyl Hydroxylase Domain 2 (PHD2), which orchestrates cellular responses to varying oxygen levels. The primary aim of this investigation is to utilize gut siderophores as inhibitors of PHD2 in ischemic conditions. This study also helps in understanding the structural mechanisms by which gut microbiota regulate HIF-1α via PHD2 inhibition through the secretion of siderophores. We explore potential PHD2 inhibitors through in-silico approaches, specifically molecular docking, binding pose metadynamics, molecular dynamics simulations, and free energy calculations. We evaluated siderophores secreted by gut microbiota as candidate inhibitors for PHD2. Docking studies revealed that Salmochelin SX exhibits the highest binding affinity to PHD2 (− 9.527 kcal/mol), interacting with key residues such as ASP254, TYR310, ASP315, and ARG322. Despite its high affinity, binding pose metadynamics indicated instability for Salmochelin SX, whereas Staphyloferrin A demonstrated superior stability. Molecular dynamics simulations confirmed stable ligand interactions with PHD2, highlighting HIS313 and ASP315 as critical for inhibition. Principal Component Analysis (PCA) and Free Energy Landscape (FEL) analyses underscored conformational changes and binding stability, suggesting that these interactions may stabilize PHD2’s active site and have potential therapeutic implications. Additionally, the study reveals how gut microbiota prevent gut dysbiosis through the stabilization of HIF-1α signaling by secreting siderophores.